Rangkap Status Muzaki Dan Mustahik Pada Pendistribusian Zakat - Restia Gustiana (ITB AAS INDONESIA Surakarta, 2023)
Penelitian ini bertujuan untuk menelusur lebih jauh rangkap status antara muzaki atau orang yang diwajibkan berzakat dengan mustahik yaitu orang yang berhak diberi harta zakat. Penelitian ini menggunakan metode kualitatif, pendekatan penelitian yang digunakan dalam penelitian ini adalah pendekatan sosiologi-hukum yakni pendekatan yang berhubungan dengan gejala sosial yang This study aims to explore further the dual status between muzaki or people who are obliged to pay zakat and mustahik, namely people who are entitled to be given zakat assets. This study uses a qualitative method, the research approach used in this study is a socio-legal approach, namely an approach related to social phenomena that occur in society which is then studied from a legal perspective related to these social phenomena. The results of this study indicate that there is a dual status that occurs in society related to the distribution of zakat itself. This dual status results in unequal welfare of the mustahik. Of course, if this continues without any bright spot, it will become an unresolved fiqh issue and further distance from the target of improving people's welfare because it cannot provide legal certainty for them. This requires special attention from Muslim scholars, or academics to complete or rectify the thirst for knowledge of the community, especially for the amil so that they can act properly, because the amil have not found the answers they need to answer this question. So that there is a common understanding and perception in dealing with this issue. This dual status is closely related to the perfection of worship for Muslims in terms of paying zakat assets because it is related to the validity of their worship.